2023
DOI: 10.1021/acsaem.3c00687
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescent Waveguide Lattices for Enhanced Light Harvesting and Solar Cell Performance

Abstract: We present the properties and performance of fluorescent waveguide lattices as coatings for solar cells, designed to address the significant mismatch between the solar cell’s spectral response range and the solar spectrum. Using arrays of microscale visible light optical beams transmitted through photoreactive polymer resins comprising acrylate and silicone monomers and fluorescein o,o′-dimethacrylate comonomer, we photopolymerize well-structured films with single and multiple waveguide lattices. The materials… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…Recently, active luminescent WELs, herein referred to as LWELs, have also been demonstrated based on a binary photopolymer blend of the acrylate-based commercially available Norland Optical Adhesive 65 (NOA 65) and an epoxide-terminated polydimethylsiloxane (PDMS) oligomer. 29 Camphorquinone (CQ) was used as the free-radical photoinitiator, together with (4octyloxyphenyl)phenyliodium hexafluoroantimonate (OPPI) as co-initiator, to drive the epoxide end-group photopolymerization of PDMS. The luminophore fluorescein o,o′-dimethacrylate was also included in the blend (assumed to graft to NOA 65), which enables spectral conversion of incident UV-blue light to green photoluminescence in the final material.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, active luminescent WELs, herein referred to as LWELs, have also been demonstrated based on a binary photopolymer blend of the acrylate-based commercially available Norland Optical Adhesive 65 (NOA 65) and an epoxide-terminated polydimethylsiloxane (PDMS) oligomer. 29 Camphorquinone (CQ) was used as the free-radical photoinitiator, together with (4octyloxyphenyl)phenyliodium hexafluoroantimonate (OPPI) as co-initiator, to drive the epoxide end-group photopolymerization of PDMS. The luminophore fluorescein o,o′-dimethacrylate was also included in the blend (assumed to graft to NOA 65), which enables spectral conversion of incident UV-blue light to green photoluminescence in the final material.…”
Section: Introductionmentioning
confidence: 99%
“…30 In the LWEL system, the addition of fluorescein increases this refractive index contrast, likely due to increased phase separation or a greater refractive index across the sample, especially along the waveguide channels. 29 This is perhaps unsurprising since it is well-known that absorption spectrum overlap between the photosensitizer and embedded luminophore (as is the case for CQ and fluorescein) affects both the cure depth and degree of photopolymerization. 18,31 For example, detailed studies by Lalevée and co-workers demonstrated that fluorescent dyes from the naphthalimide family could influence the photoinitiation of methacrylates, acrylates and their blends systems, using both free-radical and cationic polymerization mechanisms, which affected both the integrity and mechanical properties of 3D-printed structures; however, the fluorescence properties were not investigated in detail.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, active luminescent WELs, herein referred to as LWELs, have also been demonstrated based on a binary photopolymer blend of the acrylate-based commercially available Norland Optical Adhesive 65 (NOA 65) and an epoxide-terminated polydimethylsiloxane (PDMS) oligomer. 29 Camphorquinone (CQ) was used as the free-radical photoinitiator, together with (4-octyloxyphenyl)phenyliodonium hexafluoroantimonate (OPPI) as co-initiator, to drive the epoxide end-group photopolymerization of PDMS. The luminophore fluorescein o,o′-dimethacrylate was also included in the blend (assumed to graft to NOA 65), which enables spectral conversion of incident UV-blue light to green photoluminescence in the final material.…”
Section: Introductionmentioning
confidence: 99%
“… 30 In the LWEL system, the addition of fluorescein increases this refractive index contrast, likely due to increased phase separation or a greater refractive index across the sample, especially along the waveguide channels. 29 This is perhaps unsurprising since it is well known that absorbance spectrum overlap between the photosensitizer and embedded luminophore (as is the case for CQ and fluorescein) affects both the cure depth and degree of photopolymerization. 18 , 31 For example, detailed studies by Lalevée and co-workers demonstrated that fluorescent dyes from the naphthalimide family could influence the photoinitiation of methacrylates, acrylates, and their blend systems using both free-radical and cationic polymerization mechanisms.…”
Section: Introductionmentioning
confidence: 99%